Potential, Challenges, and Opportunities of a Philippine State University in Central Philippines as a Farm Tourism Destination - Canson, Maria Cristina; Caelian, Merlita V. (Technium Social Sciences Journal, 2024)
Farm tourism also called agritourism is a growing business globally with limited expansion in the South Asian region. It is valuable as a form of leisure and as facilitator of sustainable rural development, sustainable agriculture and food security. Educational institutions abroad are exploring the potential of agritourism to catalyze development, facilitate learning and generate income. This explanatory mixed method sequential inquiry assessed the level of potential of a state university as an accredited farm tourism destination based on the Philippine’s Department of Tourism (DOT) standards for day farms and farm stays in terms of the 6As: attractions, accessibility, accommodation, activities, amenities, and accountability. For the quantitative part, the researcher used a researcher-made instrument based on the DOT-Department of Agriculture Rules and Regulations Governing the Accreditation of Farm Tourism Camps. For the qualitative part, the researcher used a semi-structured in-depth one-on-one interview. Quantitively, results determined that the state university has high potential to be accredited as farm tourism destination. Qualitatively, results revealed that the potential is due to its agriculture program, area and farm attractions. It is also due to the high presence of some supporting As of tourism. The challenges in tourism development are design and development of the attractions and inadequacy of the As. Nonetheless, accreditation is still possible. Also, it emerged that tourism offers internal and external opportunities. In conclusion, universities may become DOT-accredited tourist destinations if they possess attractive qualities. This is because academic institutions have a built-in readiness for tourism. Specifically, universities offering agriculture program or course may consider operating agritourism. Though there are challenges, these only signal a need for deliberate tourism planning on the part of the institution. Finally, the DOT accreditation process must be pursued in order that the potential of a destination for tourism may be fully realized.